9/11 and the design of counterterrorism institutions - Karlsson, Michael (Ashgate Pub., 2012)
How did the North European states react to the terrorist attacks in the United States on September 11, 2001? The author argues that 9/11 led to a considerable pressure to strengthen rules and practices for counterterrorism and security, but that this pressure was mediated by several other conditions.